Citizen science in river monitoring: a systematic literature review of the whys and hows - Shao, Gabrielle Pengyu; Bishop, Isabel J. (Frontiers in Environmental Science, 2025)
River monitoring is a prevalent focus within citizen science projects. Despite numerous reports and institutional manuals detailing the monitoring techniques employed in individual projects, there is a notable lack of comprehensive academic research on the diverse methods and objectives utilized by citizen scientists in river monitoring. This study conducts a systematic literature review to clarify the specific objectives of these citizen science projects and the primary methods used to achieve each objective. We followed the PSALSAR methodology for systematic reviews in environmental science to assess information on global citizen science initiatives in river monitoring available in both published and grey literature. We ultimately reviewed 97 documents from three databases: Web of Science, Google Scholar, and Google. These documents revealed a dominant focus among river-based citizen science projects on objectives related to water quality and river ecosystem health. Methods were varied, and many common methods are routinely applied to multiple objectives. The study provides a framework that links the main objectives to the primary methods, serving as both a practical guide for new initiatives and a valuable index for academic research.